Integrating Islamic Family Law and Gender Equality: A Comparative Study of Legal Reform and Social Norms in Contemporary Indonesia and Morocco - Ahmad Ash Shiddieqy; Akhmad Roja Badrus Zaman; Sumayyah Faqihah; Muhammad Nur Fathoni; Dinda Difia Madina (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose - This study analyzes how the reform of the Islamic family law framework in Indonesia and Morocco interprets and accommodates gender equality values in their respective socio-legal contexts. Method – This study uses qualitative methods and literature analysis. The main sources include the Indonesian Marriage Law No. 1 of 1974 and the Moroccan Family Code of 2004 (Mudawwanah al-Usrah). The data were analyzed thematically to identify similarities and differences in the rules and application of gender-inclusive legal norms in Indonesia and Morocco. Findings – Both legal systems are rooted in Islamic Sharia principles and provide formal protections for women and children, such as women's right to file for divorce and the priority of children's welfare in custody decisions, but they differ in the structure of gender relations. Morocco has adopted an egalitarian model that recognizes wives as legal partners equal to their husbands. Meanwhile, Indonesia maintains a hierarchical model in which the husband is placed as the head of the family, reflecting the patriarchal norms that still prevail. This difference highlights the interaction between legal reform and the dominant social and cultural logic. Research implications – This study offers critical insights into the capacity of Islamic family law to adapt to greater gender inclusivity. Originality/value – This study contributes to the discourse on Islamic legal reform by illustrating how gender equality can be negotiated within sharia-based legal systems.